Sedimentation and carbon accumulation rates in UK saltmarshes - Cai Ladd (EGU General Assembly 2023, Vienna, Austria, 24–28 Apr 2023)
Saltmarshes play a key role in sequestering and storing carbon, as well as providing a wide range of other ecosystem services. Assessments of both total carbon stocks and rates of carbon accumulation are vital for quantifying saltmarsh contributions to climate-change mitigation and for guiding efforts to protect and restore coastal wetlands. Current assessments of the rates at which UK saltmarshes accumulate carbon are based on a small and spatially limited dataset. To address this knowledge gap, we estimate sedimentation rates and assess organic carbon density from 22 saltmarshes distributed around the UK. Bayesian modelling quantifies the relationship between depth and age from 210Pb and 137Cs activity data. We combine these sedimentation rates with centimetre-resolution organic carbon density measurements to quantify carbon accumulation rates through time. By upscaling these estimates to the total UK saltmarsh area and fully quantifying uncertainties, we conclude that UK saltmarsh carbon burial rates are lower than previously thought.